Development of Problem-Based E-Worksheet Assisted by GeoGebra to Improve Numeracy Literacy and Student Learning Activeness in Junior High School - Dyana Astuti; Yumiati; Sudirman (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
This research aims to develop a problem-based electronic worksheet (E-Worksheet) assisted by GeoGebra to enhance students' numeracy literacy and learning activeness in junior high school. The development procedure follows the ADDIE model, including analysis, design, development, implementation, and evaluation stages. Validation by experts shows the E-Worksheet is very feasible to use, with an average validation score of 4.46 out of 5. Practicality is confirmed through positive responses from teachers and students, scoring above 4.5. Effectiveness testing through a quasi-experimental design indicates a significant improvement in students’ numeracy literacy and learning activeness when using the developed E-Worksheet compared to the control group. These findings suggest that the developed E-Worksheet can be a valuable learning resource to improve mathematical literacy and student engagement in learning.